The dragon lantern : a League of Seven novel - Gratz, Alan, 1972- (Starscape, 2016)
Archie Dent and his friends Hachi and Fergus, the first three members of a new League of Seven, a group of heroes who come together to fight the Mangleborn whenever the monsters arise to destroy humanity, undertake separate missions and in the course of their adventures meet potential candidates to join their League, while learning deep-rooted secrets that could destroy the League forever.